1984
DOI: 10.1159/000176840
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Transfer to the Fetus and to the Amniotic Fluid in Rhesus Monkey <i>(Macaca mulatto)</i>

Abstract: The mechanisms of the fetal transmission of vitamin A were investigated by injecting 125I-retinol-binding protein (RBP), 131I-prealbumin and 3H-retinol-RBP in 9 pregnant rhesus monkeys. Samples of blood, amniotic fluid, and when needed fetal liver and kidney were collected after 2.5–48 h. 125I-RBP and 131I-prealbumin were detected in fetal plasma and amniotic fluid already in the first samplings. The specific radioactivity of fetal RBP increased during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 34 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…The mechanisms of transplacental flux of vitamin A are still not well-understood. Studies in rat (139) and monkey (144) have indicated that maternal retinol-binding protein crosses the placenta. The human placenta expresses surface receptors that bind retinolbinding protein (141), and the transplacental flux of the retinol-binding protein complex may be the main pathway for vitamin A transport across the placenta early in pregnancy.…”
Section: Lipid-soluble Vitaminsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of transplacental flux of vitamin A are still not well-understood. Studies in rat (139) and monkey (144) have indicated that maternal retinol-binding protein crosses the placenta. The human placenta expresses surface receptors that bind retinolbinding protein (141), and the transplacental flux of the retinol-binding protein complex may be the main pathway for vitamin A transport across the placenta early in pregnancy.…”
Section: Lipid-soluble Vitaminsmentioning
confidence: 99%
“…Fetal retinol-binding protein production occurs later in gestation (139). A second proposed mechanism for placental vitamin A transport is that the maternal retinol-binding protein binds to its receptor and releases retinol into the syncytiotrophoblast without the protein being internalized (144). The placenta then forms a retinyl ester that is secreted into the fetal circulation as lipoprotein.…”
Section: Lipid-soluble Vitaminsmentioning
confidence: 99%
“…Vitamin-A deficiency results in a predictable se quence of progressive changes in the epithe lial lining of pulmonary conducting airways [1][2][3]. These changes, classically described as necrotizing tracheobronchitis in early stages and squamous metaplasia in more advanced stages of the deficiency, are reversible with restoration of normal vitamin A status [4], Studies in various animal species have shown a transfer of vitamin A from mother to fetus during pregnancy, particularly in late gestation [5][6][7][8][9][10][11]. Although as much as 90% of total body reserve of vitamin A is found in the liver [12], it is suggested that other organs, including the developing lungs, may be capable of vitamin-A uptake, esteri fication, and storage [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This question has been approached in animal models (sheep, mouse, monkey), but the placental metabolism of retinoids is difficult to deduce from studies in the intact animal, and extrapolation of these results to humans is uncertain (11)(12)(13). Measurements of human placental, maternal, and cord retinoid concentrations have been reported, but they shed little light on the metabolic pathway (14,15).…”
mentioning
confidence: 99%